2016
DOI: 10.5897/ajar2016.11424
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of local and introduced plantains, dessert, cooking and beer bananas (Musa spp.) across different altitude and soil conditions in eastern Democratic Republic of Congo

Abstract: Agronomic performances of local and exotic

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 21 publications
3
4
1
Order By: Relevance
“…Alvarez et al (2011) worked with the cultivar 'Curare Enano', in Mexico, and encountered a plant height of de 2.73 m, which is above what was observed in the present study. Kamira et al (2016), in the eastern part of the Democratic Republic of Congo, worked with the plantains FHIA 21, Obubit and Musheba and observed an average of 2.98 m, which is similar to what was observed in Cruz das Almas (3.07 m). Short genotypes are preferred by farmers because there is no need for support and the increase in planting density results in greater economic return (Amorim et al, 2013).…”
Section: Resultssupporting
confidence: 78%
See 3 more Smart Citations
“…Alvarez et al (2011) worked with the cultivar 'Curare Enano', in Mexico, and encountered a plant height of de 2.73 m, which is above what was observed in the present study. Kamira et al (2016), in the eastern part of the Democratic Republic of Congo, worked with the plantains FHIA 21, Obubit and Musheba and observed an average of 2.98 m, which is similar to what was observed in Cruz das Almas (3.07 m). Short genotypes are preferred by farmers because there is no need for support and the increase in planting density results in greater economic return (Amorim et al, 2013).…”
Section: Resultssupporting
confidence: 78%
“…Under conditions in Guanambi (BA), the cultivar 'D´Angola' had a pseudostem diameter close to what was observed in the present study (Faria et al, 2010). In contrast, Alvarez et al (2011) reported that the cultivar 'Curare Enano' had a pseudostem diameter of 17.5 cm and Kamira et al (2016), in the Congo, reported values of 22.10 cm for the plantains FHIA 21 and Oububit, which is below what was observed under the conditions in Cruz da Almas (Brazil). Pseudostem diameter is related to tipping and/or breaking caused by wind and reflects the ability of the plant to sustain the bunch, and could be inferred based on the genetic variability for this characteristic among the genotypes evaluated (Silva et al, 2016).…”
Section: Resultssupporting
confidence: 65%
See 2 more Smart Citations
“…in North Kivu province (NK). The soil characteristics of these sites are described in detail in Kamira et al (2016).…”
Section: Methodsmentioning
confidence: 99%